Conformational stability of hemocyanins regulates their lysosomal and proteasomal degradation, influencing their pro-inflammatory effects on mammalian antigen-presenting cells - Salazar, Michelle L.; d’Alençon, Claudia; Díaz-Dinamarca, Diego; Bustamante, Javier; Castillo, Byron; Alvarado, Alejandra; Salazar, Fabián; Manubens, Augusto; Becker, María Inés (Frontiers in Immunology, 2025)
IntroductionMollusk hemocyanins are known for their immunomodulatory properties in mammals. Their applications include serving as carrier glycoproteins, functioning as protein-based adjuvants, and acting as non-specific immunostimulants in cancer vaccine strategies. Their immunomodulatory effects are attributed to their xenogenicity, structural complexity, high molecular mass, and glycosylations. Recent studies have begun to clarify the immunological mechanisms by which hemocyanins induce: multiligand properties arising from interactions with C-type lectins and Toll-like receptors, and the promotion of a Th1 immune response. However, the subsequent effects of hemocyanins, particularly their intracellular targeting and degradation kinetics, remain poorly understood. The present study is the first to comprehensively examine the processing of two well-characterized hemocyanins, known for their conformational stability and clinical significance: KLH from Megathura crenulata and CCH from Concholepas concholepas.MethodsWe correlated their degradation with the kinetics of the proinflammatory response they induce and their subcellular localization using the JAWS II cell line and bone marrow-derived dendritic cells (BMDCs). We utilize OVA to highlight the differences between this protein and the hemocyanins.ResultsThe results showed that KLH and CCH induced significant TNF levels after 24 hours and also promoted the secretion of IL-6 and IL-12p40 after 96 hours, along with the upregulation of CD80 and CD86. This delayed response corresponds with their slow intracellular degradation. Colocalization studies using LAMP-1 demonstrated that hemocyanins were localized to lysosomes only after prolonged stimulation, suggesting that they are likely stored in intracellular depots. Furthermore, hemocyanins were shown to colocalize with LMP-2 and a4, indicating that they undergo processing in the proteasome. In contrast, OVA displayed faster degradation with mild pro-inflammatory effects within 24 hours. Pharmacological inhibition of lysosomal cathepsins or the proteasome reduced the hemocyanin-dependent secretion of IL-6 and IL-12p40. Additionally, fragmented hemocyanins led to lower, less sustained cytokine levels compared to their native form.ConclusionsThese findings emphasize that hemocyanins, owing to their complex oligomeric structure and high stability, are slowly processed by APCs, thereby contributing to their immunogenicity. This property is particularly relevant when hemocyanins are used as carriers for vaccine antigens because their delayed kinetics can enhance the magnitude, quality, and persistence of responses.